The mechanical and corrosion properties of WCCo–Al coatings formed on AA2024 using the HVOF method - Akkaş, Mehmet (IOP Publishing, 2020)
Abstract This paper investigates the microstructural, mechanical, and electrical-conductivity properties of WCCo–Al composite coatings produced on the Al alloy AA2024 using the high-velocity oxygen fuel (HVOF) thermal-spray method. In an experimental study, the amount of WCCo added to Al powders was varied between 25, 50, 75, and 100 wt%. The AA2024 used as the substrate material was cleaned in acetone solution and then subjected to a sanding process using Al2O3 sand that had a grain size of 24–35 mesh for improved bonding of the coating layer. Nitrogen was used as the powder-carrier gas. After the coating process, the substrates were cooled using high-pressure air jets. The coated samples were then compared in terms of their microstructure, phase composition, microhardness, electrical conductivity, and wear properties. The microstructure, phase composition, and surfaces of the coatings after abrasion were examined using a scanning electron microscope (SEM) and an x-ray diffractogram (XRD). The XRD results showed that the WCCo–Al coating layer was composed of Al, Al0.52Co0.48, Al30Mg23, Al0.47Co0.53, MgCuAl2, WCu2Al8, AlCo, Al12W, and BNi2 phases. The addition of WCCo increased the hardness of the coatings. For instance, the highest hardness value was measured as 1,335 HV0.2 in the coating produced using 100% WCCo. The amount of WCCo in the powder also affected the microstructure, phase composition, and hardness of the coatings. Moreover, the addition of WCCo lowered the electrical conductivity, wear rates, and friction coefficients of the coatings. In indentation tests, the hardness values of the coatings were generally found to increase with increasing applied load. In corrosion tests, the corrosion resistance of the coatings was observed to increase as the amount of WCCo in the coating layer increased. The highest peak depth was 36.94 μm in the sample coated with 100% Al, and the lowest peak depth was 6.82 μm in the sample coated with 100% WCCo. The coated materials had outstanding tribological performance compared to the uncoated ones. The increase in wear resistance provided by the coating was caused by a large amount of dispersed WC and Co.
Keywords: high velocity oxygen fuel (HVOF) spraying; wear; corrosion; Chemical technology; microhardness; TA401-492; TP1-1185; WCCo; Materials of engineering and construction. Mechanics of materials